2014
DOI: 10.1039/c4dt00884g
|View full text |Cite
|
Sign up to set email alerts
|

Highly fluorinated hydrotris(indazolyl)borate calcium complexes: the structure and reactivity heavily depend on the ligand's electronic properties

Abstract: Two series of highly fluorinated 3-substituted hydrotris(indazolyl)borate (Fn-Tp(4Bo,3R); R = Ph, n = 12; R = CF3, n = 21) complexes of calcium were synthesized by salt metathesis reactions. CaI2 reacts with 2 and 1 equiv. of Tl(F12-Tp(4Bo,3Ph)) in THF to form the homo- and heteroleptic complexes [Ca(F12-Tp((4Bo,3Ph)*))2] (1) and [(F12-Tp(4Bo,3Ph))CaI(THF)] (2), respectively. 1 has C2h symmetry due to a 1,2-borotropic shift. The reaction of CaI2 with 2 equiv. of the more electron poor Tl(F21-Tp(4Bo,3CF3)) in T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…The tris(pyrazolyl)boranates quickly conquered coordination chemistry due to the ease of synthesis and the stability of their metal complexes. Nevertheless, borotropic shifts have been observed and undesired side products have correspondingly been obtained . Recently, high‐yield protocols have been developed for the isoelectronic tris(pyrazolyl)methanes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The tris(pyrazolyl)boranates quickly conquered coordination chemistry due to the ease of synthesis and the stability of their metal complexes. Nevertheless, borotropic shifts have been observed and undesired side products have correspondingly been obtained . Recently, high‐yield protocols have been developed for the isoelectronic tris(pyrazolyl)methanes.…”
Section: Discussionmentioning
confidence: 99%
“…For the s‐block metals many derivatives have also been described, and these ligands are considered stable anions in the vicinity of metal ions. Nevertheless, borotropic shifts have recently been observed for a calcium complex, with unexpected products being obtained . Substantial use of bis(pyrazolyl)‐ and tris(pyrazolyl)methane, as well as ‐methanide ligands, is only the case for transition‐metal chemistry.…”
Section: Introduction – Scope Of the Microreviewmentioning
confidence: 99%
“…2 Ca], even though the latter exhibits one inverted indazolyl ring. [31] Despite this distortion and the low coordination number, complex 1 does not show any agostic-type interaction involving the hexamethyldisilylamido group.…”
Section: Introductionmentioning
confidence: 98%
“…[30] Two differently substituted ligands, {F n -Tp 4Bo, 3R } À (R = CF 3 , n = 21, and R = Ph, n = 12), have been tested on Ca, the phenyl-based ligand providing the best compromise in terms of steric protection and electron-withdrawing properties (Scheme 2). [31] Earlier reports have shown that sterically encumbered, differently substituted tris(pyrazolyl)borates (Tp') coordinate Ca 2 + with the formation of heteroleptic Tp'CaX complexes. [32] A [33] These amido complexes were shown to catalyze the ring-opening polymerization of lactide, [33] but to our knowledge they have not been tested for hydroamination reactions.…”
Section: Introductionmentioning
confidence: 99%
“…For our part, we have been interested in varying the electron‐withdrawing properties of the Tp′ ligand and investigating the consequences in calcium chemistry , . We used magnesium derivatives for benchmarking in the case of hydrocarbyl derivatives .…”
Section: Introductionmentioning
confidence: 99%